2000
DOI: 10.1046/j.1365-2648.2000.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in old age described as a sense of well‐being, meaning and value

Abstract: The purpose of the study was to present a model of quality of life and related factors, to study quality of life in a group of elderly subjects, and to do preliminary testing of the model. Quality of life was defined as a sense of well-being, meaning and value. The model includes health, functional capacity, and coping mechanisms as intra-individual conditions for quality of life, while factors in the biophysical and sociocultural environment are described as external conditions. The study sample consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
1
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 21 publications
4
112
1
9
Order By: Relevance
“…This hypothesis is emphasized by the study done by Alzahrani et al (2013) as they found that there was a strong positive relationship between religious connectedness and Saudi HRQL [34]. Sarvimäki et al (2000) defined the QoL as sense of well-being which includes coping mechanisms with 2 factors; intra-individual factor and external factors as biophysical and sociocultural environment [35]. Although the external factors could not be controlled by the persons, the intra-individual factor might be enhanced by the persons' religious concepts and so improve their ability to manage successful coping mechanisms, higher emotional well-being, and better HRQoL.…”
Section: Hrqol Domains Related To Pal Among Saudismentioning
confidence: 94%
“…This hypothesis is emphasized by the study done by Alzahrani et al (2013) as they found that there was a strong positive relationship between religious connectedness and Saudi HRQL [34]. Sarvimäki et al (2000) defined the QoL as sense of well-being which includes coping mechanisms with 2 factors; intra-individual factor and external factors as biophysical and sociocultural environment [35]. Although the external factors could not be controlled by the persons, the intra-individual factor might be enhanced by the persons' religious concepts and so improve their ability to manage successful coping mechanisms, higher emotional well-being, and better HRQoL.…”
Section: Hrqol Domains Related To Pal Among Saudismentioning
confidence: 94%
“…노인에게서의 삶의 질은 행복감, 가치관, 자존감으로 정의 되기도 한다 [7]. 이러한 노인의 삶의 질과 관련이 있는 스트레 스와 우울은 노인의 자살생각을 유도하는 요인이 되기도 한다 [8].…”
unclassified
“…A conceptual framework was found in only 13% of the studies (Beaumont and Kenealy 2004;Grundy and Bowling 1999;Higgs et al 2003;Nesbitt and Heidrich 2000;Sarvimaki and Stenbock-Hult 2000). Of the six studies reviewed, Grundy and Bowling (1999) described QoL in relation to different models of human needs, as reflected in Maslow's theory (1954), and satisfaction with life and happiness as accompanying successful aging.…”
Section: Conceptual Framework Of Qolmentioning
confidence: 99%
“…In the studies that reviewed age-specific areas, discussion was focused on physical or physiological changes (Berlowitz 1995;Brazier et al 1996;Grimby and Wiklund 1994;Liu-Ambrose et al 2005;Stenzelius et al 2005); role and developmental changes (Grimby and Wiklund 1994;Grundy and Bowling 1999;Noro and Aro 1996;Sarvimaki and Stenbock-Hult 2000); cognitive and mental functioning (Brazier et al 1996;De Leo et al 1998;Noro and Aro 1996); changes in social network (Dempster and Donnelly 2000); changes in functional ability (Borglin et al 2005;Liu-Ambrose et al 2005;Stenzelius et al 2005); need for control, autonomy, pleasure, and self-realization (Higgs et al 2003); pain (Liu-Ambrose et al 2005); residential arrangements and social comparison processes (Beaumont and Kenealy 2004); and sight, hearing, communication, and fatigue as considerations in administration (Tidermark et al 2004). Also, considerations given to education, value orientations, work, and an understanding of health as differing from younger samples were made (Beaumont and Kenealy 2004;Berlowitz 1995;Bowling et al 2002;Brazier et al 1996;Byles 1999;De Leo et al 1998;Higgs et al 2003).…”
Section: Psychometric Properties Reliability and Validitymentioning
confidence: 99%
See 1 more Smart Citation